2010
DOI: 10.1073/pnas.1000771107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene essential for protoporphyrinogen IX oxidase activity in the cyanobacterium Synechocystis sp. PCC6803

Abstract: Protoporphyrinogen oxidase (Protox) catalyses the oxidation of protoporphyrinogen IX to protoporphyrin IX during the synthesis of tetrapyrrole molecules. Protox is encoded by the hemY gene in eukaryotes and by the hemG gene in many γ-proteobacteria, including Escherichia coli. It has been suggested that other bacteria possess a yet unidentified type of Protox. To identify a unique bacterial gene encoding Protox, we first introduced the Arabidopsis hemY gene into the genome of the cyanobacterium, Synechocystis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 33 publications
0
54
0
Order By: Relevance
“…Kato et al recently identified HemJ in Synechocystis in this fashion by introducing plant-derived acifluorfen-sensitive PPO into cells and then screening mutants for acifluorfen sensitivity (24). This approach is suited for the identification of novel enzymes where a second, well-characterized enzyme exists that catalyzes the reaction of interest and for which a novel inhibitor also exists, but it does not easily lend itself to all enzyme systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kato et al recently identified HemJ in Synechocystis in this fashion by introducing plant-derived acifluorfen-sensitive PPO into cells and then screening mutants for acifluorfen sensitivity (24). This approach is suited for the identification of novel enzymes where a second, well-characterized enzyme exists that catalyzes the reaction of interest and for which a novel inhibitor also exists, but it does not easily lend itself to all enzyme systems.…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al (24) noted that they could not identify hemJ, hemG, or hemY in Archaea, Actinobacteria, Acidibacteria, Deinococcus, Fusobacteria, Spirochaetes, and Thermotogae and posited that these organisms may contain other, yet-to-beidentified, novel PPO enzymes. This is clearly true in Archaea, where, with limited exceptions, the organisms do not possess HemF/N, HemG/Y/J, or HemH as the terminal pathway enzymes essential for protoheme biosynthesis but instead utilize a different pathway from uroporphyrinogen to heme that involves S-adenosyl-L-methionine-dependent uroporphyrinogen III methyltransferase, precorrin-2 dehydrogenase, and the ahbnir genes (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, relatively little is known about PgdH2. It is a membrane-bound protein but may require a soluble factor for activity (278,279). This protein has not been purified to homogeneity, and there are no data to support the presence or absence of a cofactor.…”
Section: Prokaryotic Heme Biosynthesismentioning
confidence: 99%
“…Currently three types of PPO have been reported: HemG (Boynton et al 2009), HemJ (Kato et al 2010), and HemY (Lermontova et al 1997;Narita et al 1996). While HemG and HemJ are both primarily of bacterial origin, HemY is found in both eukaryotes and prokaryotes.…”
Section: Protoporphyrinogen IX Oxidasementioning
confidence: 99%